Tumor response to a mastermind inhibitor protein - Epenetos, Agamemnon; Prokopi, Marianna; Pitsillides, Costas; Kapnisis, Konstantinos; Deonarain, Mahendra; Kousparou, Christina; Anayiotos, Andreas (My University, 2020)
Notch signalling is implicated in tumorigenesis prompting scientists to research and develop anti-Notch therapeutics. Drugging the Notch pathway has been a challenge due to severe G-I toxicity seen by many small-molecule inhibitors. Mastermind is a key nuclear factor that mediates Notch activity. We generated a novel protein drug, Syntana-4, that inhibits the Notch pathway at the Mastermind transcriptional level. Syntana-4 consists of the cell penetrating domain of Antennapedia, fused to a truncated peptide from Mastermind-like (MAML) that behaves in a dominant-negative fashion inhibiting Notch. Syntana-4 translocates into the cell nucleus, suppressing Notch activity and inducing apoptosis in Notch-driven cancer cells. Methods: We have conducted pharmacokinetics (PK), pharmacodynamics (PD) and toxicology studies, in combination with innovative imaging including in vivo flow cytometry and whole-body fluorescence reflectance imaging to define the behaviour of Syntana-4, determine its mode of action and establish a safety and efficacy profile in an orthotopic model of breast cancer in SCID mice based on the implantation of MDA-MB-231 cells into mammary fat pads. Samples of blood and tissues were examined for toxicity, apoptosis and immunogenicity. Results: We found that Syntana-4 was well-tolerated by normal cells and organs and was not immunogenic. Also, it was shown that free, non-internalized drug was rapidly cleared from the circulation. Whole body imaging showed that the drug in tissues was cleared within 24 hrs. Assessment of tumor growth demonstrated a reduction in tumor growth as evidenced by an overall increase of less than 50% in the intensity of fluorescence signal in the treated group compared to a 3-fold increase in signal and thus tumour size in untreated group by day 14. Conclusions: Syntana-4, a Mastermind inhibitor, was found to be well-tolerated and non-immunogenic in healthy animals. This drug targets the oncogenic Notch mechanism and can be applied across tumours with genetic defects in Notch signalling including breast, prostate, etc. We have demonstrated the utility of an innovative molecular imaging system emulating a clinical ‘phase I/II’ study in an orthotopic cancer model in order to measure the biodistribution, PK, PD, mode of action, toxicity and efficacy of a first-in-class biological therapy prior to entering the clinic. This innovative approach could be useful for accurate selection of lead drug candidates prior to entering clinical development.